Consumption Compliance of Ferrum Tablet with Anemia in Pregnant Woman in Ngasinan Village Sukoharjo Central Java - Anik Sulistiyanti; Ana Yuliana (LPPM Universitas Duta Bangsa Surakarta, 2019)
Iron deficiency called anemia is still a health problem in Indonesia which has a bad impact on sufferers, especially in pregnant women. Pregnant women affected by anemia reach 40% -50%, meaning that 5 out of 10 pregnant women in Indonesia suffer from anemia. Fe tablets or blood booster tablets are 60 mg of iron and 0.5 mg of folic acid given orally or commonly referred to as oral iron therapy. The iron content in Fe tablets is greater than that of folic acid, this is because iron deficiency anemia is the main cause of anemia in pregnant women compared to other iron deficiencies. The purpose of this study to find out the compliance of Fe tablets consumption with the incidence of anemia in pregnant women and the difference in the incidence of anemia after giving Fe tablets to pregnant women. This type of research is a quasi-experimental two group pretest-posttest design research design. The study population was all pregnant women in the village of Ngasinan, Sukoharjo. The research sample was 35 pregnant women with random sampling techniques. Collecting data using examination of hemoglobin levels and a closed questionnaire. Data analysis with univariat analysis and multivariat analysis using one way anova. The results of the one way anova test results obtained F count was 19,735 with a significance of 0,000. In the hypothesis test the test decision is if F arithmetic > F table or significance value ≤ 0.05. There is a significant difference between compliant in consuming Fe tablets with the incidence of anemia in pregnant women.